Analysis of FIFA 2023 Women’s World Cup match performance according to match outcome and phase of the tournament - José M. Oliva-Lozano; Farzad Yousefian; Paweł Chmura; Tim J. Gabbett; Rick Cost (Biology of Sport)
The aim of the study was to analyze the FIFA 2023 Women’s World Cup match performance according to match outcome and phase of the tournament. Match performance data were analyzed from a total of 64 games, which included a total of 32 national teams. The variables collected from the post-match summary reports were calculated according to match time (i.e., data per minute) and were categorized in four groups: key statistics, in possession and out of possession variables, out of possession defensive pressure variables, and physical performance variables. When it comes to match outcome, significant differences were observed in key statistics (e.g., there were significantly greater possession, goals, attempts at goal on target, total passes, total passes completed, defensive line breaks, and receptions in the final third when winning compared to drawing or losing), in possession variables(e.g., winsshowed significantly greater build up unopposed compared to losses and draws), out of possession variables (e.g., wins showed significantly greater high press than losses), and out of possession defensive pressure variables (e.g., losses showed significantly greater total pressure, pressing direction outside, and ball recovery time compared to wins or draws). There were no significant differences in any physical performance variable, except for distance covered in zone 1 (losses > draws). When it comes to the phase of the tournament, no significant differences were observed in any variable, except for distance covered in zone 1 (knock-out > groups). Furthermore, significant interactions were observed between match outcome and phase of the tournament in the following variables: attempts at goal on target, pass completion %, progressions, and average pressure duration. Quantifying and comprehending match-play characteristics hold significant importance in guiding practices within women’s soccer. Therefore, this study serves as a resource for the staff of national teams to understand performance according to match outcome and phase of the tournament in an international women’s soccer tournament.